2023
DOI: 10.1101/2023.02.03.527064
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fecal virome transplantation is sufficient to alter fecal microbiota and drive lean and obese body phenotypes in mice

Abstract: Background: The gastrointestinal microbiome plays a significant role in numerous host processes and has an especially large impact on modulating the host metabolism. Prior studies have shown that when mice receive fecal transplants from obese donors that were fed high-fat diets (HFD) (even when recipient mice are fed normal diets after transplantation), they develop obese phenotypes. These studies demonstrate the prominent role that the gut microbiota play in determining lean and obese phenotypes. While much o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…For instance, FVT influenced the composition of the murine gut microbiome following initial perturbation with antibiotics [15]. Additionally, FVT treatment from lean donors alleviated symptoms of metabolic syndrome in three different diet-induced obesity murine models [1618], and FVT from term piglets prevented the development of necrotizing enterocolitis in a preterm piglet model [19]. FVT has the advantage over FMT in that it significantly diminishes the transfer of viable bacteria, and FVT has recently been demonstrated to be less intrusive for both the gut microbial structure and linked to a reduced likelihood of causing harm to the jejunum in broiler chickens compared to FMT [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, FVT influenced the composition of the murine gut microbiome following initial perturbation with antibiotics [15]. Additionally, FVT treatment from lean donors alleviated symptoms of metabolic syndrome in three different diet-induced obesity murine models [1618], and FVT from term piglets prevented the development of necrotizing enterocolitis in a preterm piglet model [19]. FVT has the advantage over FMT in that it significantly diminishes the transfer of viable bacteria, and FVT has recently been demonstrated to be less intrusive for both the gut microbial structure and linked to a reduced likelihood of causing harm to the jejunum in broiler chickens compared to FMT [20].…”
Section: Introductionmentioning
confidence: 99%
“…FVT has the advantage over FMT in that it significantly diminishes the transfer of viable bacteria, and FVT has recently been demonstrated to be less intrusive for both the gut microbial structure and linked to a reduced likelihood of causing harm to the jejunum in broiler chickens compared to FMT [20]. In addition to the viruses, these FVT preparations would also be expected to contain a certain level of bacterial spores and cells with sizes that allow them to pass through the 0.45 µm filter membrane pores, fecal metabolites, and extracellular vesicles of which contributions to the observed effects following FVT [12,13,[15][16][17][18][19][20][21]] are yet to be elucidated. Furthermore, the sterile filtration process commonly used in FVT does not eliminate the risk of transferring eukaryotic viruses, which previously have been detected in specific pathogen-free mice [22].…”
Section: Introductionmentioning
confidence: 99%
“…This approach is often referred to as fecal virome transplantation (FVT). In preclinical settings, FVT has also been shown to alleviate symptoms of type-2 diabetes and obesity in male mice 25,26 , prevent the onset of necrotizing enterocolitis in preterm piglets 7 , restore the GM after antibiotic intervention 27 , and improve the proliferation of commensal gut Akkermansia muciniphila 28 . These findings highlight the promising application of FVT as a GM restoring treatment targeting various diseases associated with GM dysbiosis.…”
Section: Introductionmentioning
confidence: 99%
“…In mice, the FVT reduced intestinal bacterial overgrowth [17] and improved weight and glucose tolerance in type 2 diabetes [15]. The FVT can also change gut bacteria and drive lean and obese body phenotypes [20]. However, these experiments only involved FVT from mice to mice and human to human.…”
Section: Discussionmentioning
confidence: 99%
“…FVT has also shown promising results in treating metabolic diseases such as type 2 diabetes (T2D) and obesity, decreasing weight gain, and normalizing blood glucose tolerance in diet-induced obese mice [19]. It has also been demonstrated that FVT can change fecal microbiota and induce lean and obese body phenotypes in mice [20]. On the other hand, human studies have found that FVT from healthy and lean donors can improve glucose levels in individuals with MetS [21].…”
Section: Introductionmentioning
confidence: 99%